Managers' Practices of Tobacco and Marijuana Smoking Policies in Hispanic-Occupied Multiunit Housing - Angelica Delgado Rendon; Tess Boley Cruz; Lourdes Baezconde-Garbanati; Claradina Soto; Jennifer B. Unger (Mary Ann Liebert, 2019)
Purpose: This study assessed the knowledge, attitudes, and practices of managers of Hispanic-occupied multiunit housing (MUH) related to the prevalence and prevention of secondhand smoke (SHS), thirdhand tobacco smoke, and secondhand marijuana smoke (SHMS). Methods: A narrative analysis was conducted of 20 interviews with live-in apartment managers. Their opinions on policies and an educational fotonovela were also gathered. Results: The properties were located in 10 cities within the Los Angeles County, representing a wide array of local policies and practices. Only two managers were correctly informed of the existing MUH smoking policies in their cities. Participants reported ambiguity in city laws and company rules regarding smoking. Managers do not distinguish between smoking recreational marijuana and medicinal marijuana. Several respondents believed the landlords have more power to create rules. Most favored a total ban on smoking of all substances on the premises. Conclusions: Most managers report low agency in being able to pass no-smoking rules. Participants support smoking policies that include all smokable products. Managers would like new government policies, manager trainings, tenant education, and ways to enforce rules to protect apartment tenants from SHS and SHMS. Educational interventions should coincide with the timing of key manager/tenant activities. Results can be used in policy development and educational interventions.